Nutritional lifestyle patterns and cancer: confounding effect of social determinants across the life course in women from the 1958 British birth cohort study - Carayol, Marion (2020)
Objective: To examine the confounding role of social determinants across the life course in the relationship of nutritional lifestyle patterns with cancer in women. Methods: In the National Child Development Study, 37 items regarding diet, alcohol and physical activity frequencies were recorded at ages 33 and 42 years. Some 6,169 women were included and 237 women reported cancer diagnosis before age 55 years. Cancer odds ratios (OR) were estimated by logistic regression for the highest versus the lowest tertile of nutritional lifestyle pattern score. Social determinants from birth to adulthood were introduced as potential confounders in logistic models using a life-course approach. Results: Four nutritional lifestyle patterns were identified: ‘Healthy active’, ‘Drinker’, ‘Sweet tooth’ and ‘Western’. The ‘Drinker’ pattern was significantly associated with increased cancer risk: covariates-adjusted OR = 1.65 (95% CI: 1.17–2.33; p = .004); ptrend = .017 for all cancers combined, and 1.65 (95% CI: 1.06–2.58; p = .03); ptrend = .07 for breast cancer. These associations were attenuated after entering social determinants of birth, childhood and adulthood in the model: covariates and social variables-adjusted OR = 1.54 (95% CI: 1.08–2.18; p = .016); ptrend = .054 for all cancers combined, and 1.50 (95% CI: 0.95–2.38; p = .08); ptrend = .19 for breast cancer. The other patterns were not associated with cancer risk. Conclusion: This study demonstrates an association between the ‘Drinker’ pattern and midlife cancer in British women. Social determinants across the life course explained a part, though modest, of this association.